Molecular surveillance of malaria in Tanzania: Baseline surveillance of vectors that drive persistent malaria transmission in regions with varying transmission intensities - Yahya A. Derua; Bernard M. Batengana; Filbert Francis; Celine I. Mandara; Rashid A. Madebe; Misago D. Seth; Daniel P. Challe; Deus S. Ishengoma (PLoS ONE, 2026)
Malaria has remained persistently high in some regions of Tanzania despite increased control interventions. To address the burden of malaria in these regions, monitoring malaria vector dynamics is crucial to inform control interventions. This study assessed the composition and infectivity of malaria vectors in areas with varying levels of transmission. A cross-sectional study was conducted in five districts: Buhigwe, Kyerwa, Ludewa, Muheza, and Nyasa, from August to October 2023. In each district, one to five villages were selected for the study, and mosquitoes were collected indoors from 10 households per village using CDC light traps. Outdoor mosquitoes were collected from five households using Furvela tent traps. In all selected villages and trap types, mosquitoes were collected over three nights. Collected mosquitoes were sorted by species, and malaria vectors were sent to the laboratory for identification and screening for malaria parasites using polymerase chain reaction. A total of 19,898 mosquitoes were collected, and Anopheles gambiae complex, An. funestus group, other Anopheles species and culicine species accounted for 2.2%, 44.3%, 1.1% and 52.4%, respectively. An. funestus group was the predominant species, accounting for 95.3% of the malaria vectors. Sibling species identification revealed that An. arabiensis was the main species (75.0%) in An. gambiae complex, whereas An. funestus sensu stricto (s.s) was predominant (96.3%) in An. funestus group. A total of 1799 vectors were tested for infection with Plasmodium falciparum, and nine (0.5%) collected with CDC light traps were infected. The estimated annual entomological inoculation rate for An. funestus collected by light traps was 242.6, 66.5, and 13.0 infectious bites per person per year in Kyerwa, Nyasa, and Muheza, respectively. This study recorded a relatively high density of malaria vectors, particularly in Kyerwa district, despite being conducted during the dry season. An. funestus was the main vector, and interventions targeting it are urgently needed to achieve the national goal of malaria elimination by 2030.